Antibacterial consumption before, during, and after the COVID-19 pandemic in a tertiary care pediatric hospital in Mexico - Ana Mayra Pérez-Morales; Rodolfo Norberto Jiménez-Juárez; Olga Magdala Morales-Ríos; Alfonso Reyes-López; Patricia Clark; Erika Janet Islas-Ortega; Fernando Ortega-Riosvelasco; Heriberto Gómez-Gaytán; María del Carmen Castellanos-Cruz; Jessica Liliana Vargas-Neri (PLoS ONE, 2025)
Background During the coronavirus disease 2019 (COVID-19) pandemic, pediatric inpatients frequently received at least one antibiotic, and several antimicrobial stewardship programs (ASPs) strategies were disrupted. In Mexico, no published data are available on antibacterial consumption in children. The aim of this study was to evaluate antibacterial consumption levels and trends before, during, and after the COVID-19 pandemic in a tertiary care pediatric hospital in Mexico, and to forecast future antibacterial consumption. Methods This was a secondary analysis based on time series data of monthly antibacterial consumption from January 2016 to June 2024 in a tertiary care pediatric hospital. Antibacterial consumption was retrospectively measured for the pre-pandemic, pandemic, and post-pandemic periods. Consumption was expressed as days of therapy (DOT) per 1000 patient-days (pd). Results The mean antibacterial consumption at the Hospital Infantil de México Federico Gómez (HIMFG) from 2016 to 2024 was 789.3 (95% CI, 756.1–822.5) DOT/1000 pd. In the medical pediatric intensive care unit (M-PICU) and surgical pediatric intensive care unit (S-PICU), mean consumption was 1305.3 DOT/1000 pd (95% CI: 1119.1–1491.6) and 1634.5 DOT/1000 pd (95% CI: 1444.2–1824.9), respectively. Before the pandemic, the hospital-wide mean consumption was 848.8 DOT/1000 pd (95% CI: 811.3–886.2); during the pandemic, it was 709.6 DOT/1000 pd (95% CI: 650.3–769.0); and after the pandemic, 799.2 DOT/1000 pd (95% CI: 698.1–900.3). Overall, consumption rates oscillated around the mean, and no patterns were observed. Conclusions The COVID-19 pandemic did not affect trends of antibacterial consumption across the hospital or in the pediatric intensive care unit. Although the prior authorization component of the ASP maintained antibacterial consumption around the mean, the implementation of additional ASP strategies -such as education and persuasive interventions- alongside current restrictive measures may help further optimize antibacterial consumption in pediatric units.